Mercado De Trabalho Brasileiro Recente: Uma Análise Das Condições Da Aproximação Ao "Pleno Emprego" - Barros, Andre Correa [UNIFESP] (2018)
A Discussion About The Labor Market And The Possible Occurrence Of A Full Employment Situation Was Observed Recently In The Brazilian Economy, More Precisely Until Mid-2014, During Which The Unemployment Rate Calculated By Ibge Reached A Historically Low Mark Of 4,8%. After This Period, However, The Labor Market Has Been Registering Successive Decreases In The Generation Of Jobs, Which Consequently Contributes To A Significant Increase In The Brazilian Unemployment Rate. Given This Employment Context, The Study Aims To Contextualize The (Specific) Experience Of Growth Of The Brazilian Economy Within The Period 2002-15, As Well As The Characterization Of Jobs Generated At The Specific Moment In Which Favorable Conditions Were Observed Full Employment Situation. This Focus Was Chosen Due To The Fact That In The Face Of A Significant And Rapid Rise In The Unemployment Rate At A Later Time The Nature Of The Jobs Previously Generated Would Not Correspond To That Of Full Employment In Its Context Of Developed Econo